2006
DOI: 10.1021/jo061169j
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 2-Alkoxymethyl-5-methylphenacyl Chloride and Benzoate

Abstract: Irradiation of 2-(alkoxymethyl)-5-methyl-alpha-chloroacetophenones (1a-c) and 2-(methoxymethyl)-5-methylphenacyl benzoate (1d) in dry, nonnucleophilic solvents afforded 3-alkoxy-6-methylindan-1-ones (3a-c) in very high chemical yields. 3-Methylisobenzofuran-1(3H)-one (2) was, however, isolated as a major photoproduct in the presence of trace amounts of water. Quenching experiments and laser flash spectroscopy revealed that the indanone derivatives 3 are formed by 1,5-hydrogen migration from the lowest triplet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Therefore, this system should be suitable for novel photocleavable protecting groups48 for phosphates and alcohols. Indeed, Klán and Wirz and their co‐workers recently demonstrated that 2,5‐dimethylphenacyl esters49a49d and carbonates 49e are excellent protecting groups for carboxylic acids, phosphates, sulfonates, alcohols, and phenols. The use of 2‐methylphenacyl esters as photocleavable linkers in solid‐phase synthesis has also been reported.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Therefore, this system should be suitable for novel photocleavable protecting groups48 for phosphates and alcohols. Indeed, Klán and Wirz and their co‐workers recently demonstrated that 2,5‐dimethylphenacyl esters49a49d and carbonates 49e are excellent protecting groups for carboxylic acids, phosphates, sulfonates, alcohols, and phenols. The use of 2‐methylphenacyl esters as photocleavable linkers in solid‐phase synthesis has also been reported.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…6 A ketene intermediate was indeed observed via IR spectroscopy in a matrix isolation experiment. Time resolved spectroscopy on oPA and related compounds 15,17,18 lacked the temporal resolution to trace the ketene formation. Time resolved spectroscopy on oPA and related compounds 15,17,18 lacked the temporal resolution to trace the ketene formation.…”
Section: Introductionmentioning
confidence: 99%
“…We have opted for oABA instead of oPA since for the latter at least two rotamers (denoted as EZ and EE) coexist. 18 The computations by Blancafort et al on oPA did not take intersystem crossing (ISC) to triplet states into account. 15 For sterical reasons, in oABA the rotamer depicted in Scheme 1 is expected to predominate.…”
Section: Introductionmentioning
confidence: 99%
“…The latter reaction has recently been reported by Klan and coworkers, although only the nonnucleophilic solvents provided the cyclization products in their studies. 18 A final feature to note in photolysis of DCMA in methanol is the formation of a solvolysis product, H. A control experiment in the dark clearly showed that the reaction was light-driven, which differs from the classical haloform reaction. Our literature searches found that similar observations had been made in photolysis of α,α,α-trichloroacetophenone 19 and α,α-dichloropropiophenone.…”
Section: Resultsmentioning
confidence: 99%